How will the interaction of wages and prices play out in the last mile of disinflation? - Steven Kamin; John M. Roberts (American Enterprise Institute (AEI), 2024)
This note develops an econometric model of inflation dynamics to assess recent developments. We find that most of the rapid decline in price pressures achieved in 2023 owes to the normalization of supply chains. With supply-chain disruptions now largely resolved, future progress toward disinflation will be more difficult and will likely depend on the interplay between wages and prices. A consideration that could loom large is the shortfall in wage gains relative to their pre-pandemic trend, leading to a "wage gap" or, equivalently, a rise in firm markups over cost. Using our model, we explore different ways in which the wage gap may evolve going forward and trace out the implications of these alternative scenarios for the Fed's monetary policy. If high markups unleash important competitive pressures across firms, then inflation and thus interest rates could come down quickly. If, however, markups have a limited influence on price setting, the disinflation process could be more prolonged, as would the normalization of monetary policy. Finally, if wage gains remain elevated-perhaps motivated by attempts by workers to recover previous shortfalls in earnings-inflation and interest rates could stay high for a considerable period. Unfortunately, it isn't clear based on the econometrics or recent experience which outcome is most likely.
Keywords: 330; inflation; Monetary policy; prices; wages